Oxidative Stress Biomarkers in Chronic Obstructive Pulmonary Disease Exacerbations: A Systematic Review - Elisabetta Zinellu; Angelo Zinellu; Alessandro G. Fois; Maria Carmina Pau; Valentina Scano; Barbara Piras; Ciriaco Carru; Pietro Pirina (MDPI AG, 2021)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a progressive disease characterized by a not fully reversible airflow limitation associated with an abnormal inflammatory response. Exacerbations of COPD are of major importance in the acceleration of disease progression, in healthcare costs, and negatively affect the patient's quality of life. Exacerbations are characterized by a further increase in the airway inflammation likely driven by oxidative stress. In order to deepen the knowledge about this topic, several studies have focused on oxidative stress biomarkers levels. This review summarizes the literature findings about oxidative stress biomarkers in exacerbated COPD patients compared to ones in the stable state. Methods: a systematic search in electronic databases Pubmed, Web of Science, Scopus and Google Scholar from inception to January 2021, was conducted using the terms: "oxidative stress", "chronic obstructive pulmonary disease" or "COPD", "exacerbation". Results: 23 studies were selected for the systematic review. They showed the presence of an imbalance between oxidant and antioxidant molecules in favor of the former in exacerbation of COPD. Conclusions: future studies using standardized methods in better characterized population are needed. However, this review suggests that targeting oxidative stress could be useful in monitoring the disease progression in COPD patients and especially in those more susceptible to exacerbations.